Karl Raimund Popper: Problem Neopositivistik dan Teori Kritis Falsifikasi - Huda, M. Syamsul (Program Pascasarjana UIN Sunan Ampel Surabaya, 2007)
Karl Popper once criticizes the positivistic paradigm by means of what he calls the theory of falsification. To him, the positivistic paradigm constitutes a failure simply because it cannot distinguish between science and prude science, that is, between empirical method and non-empirical method. In the scientific knowledge, empirical science, mathematics and logic must be differentiated, something that the positivistic paradigm has failed to do. This paradigm furthermore, did not have a clear picture what logic-based science is, empirical knowledge and psychology of knowledge. It also fails to properly understand knowledge that springs from tradition, emotion, authority and so forth. All positivistic paradigms such as that of Karl Maxâs Historicism, Freudâs theory of Psycho Analysis, Adlerâs theory of Individual Analysis and Newtonâs theory of Gravitation fall into this trap of failure.